2017
DOI: 10.1177/0898264317704096
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Association Between Fear of Falling and Mobility Limitation in Relation to Late-Life Falls: A SHARE-Based Analysis

Abstract: Objectives: This study looks at fear of falling (FOF) as a predictor of falls in light of mobility limitation and other confounders. Methods: Data on community dwelling older Europeans, aged 65 and older, were drawn from two consecutive waves of the Survey of Health, Ageing and Retirement in Europe (SHARE). The analysis regressed fall status in 2013 on reported FOF two to three years earlier, controlling for previous falls. Results: FOF predicted subsequent falls when mobility limitation was low to moderat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 53 publications
(74 reference statements)
1
31
0
2
Order By: Relevance
“…Different risk factors for the occurrence of falls in older adults may act alone or in association with other factors. Studies associations of falls with female gender 2 , 4 , 6 , 7 , advanced age 4 - 6 , 10 , marital status (divorced), living alone 2 , 11 , fear of falls 12 , 13 , poor rated health 10 , 14 , depression 15 , use of medication on regular basis 10 , chronic diseases 4 , worse vision or hearing 16 , 17 , among other health problems, and inadequate environmental factors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Different risk factors for the occurrence of falls in older adults may act alone or in association with other factors. Studies associations of falls with female gender 2 , 4 , 6 , 7 , advanced age 4 - 6 , 10 , marital status (divorced), living alone 2 , 11 , fear of falls 12 , 13 , poor rated health 10 , 14 , depression 15 , use of medication on regular basis 10 , chronic diseases 4 , worse vision or hearing 16 , 17 , among other health problems, and inadequate environmental factors 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of sample size, more than half of the studies has considered samples with at most 1000 participants ( Table 3 ). Interestingly, three recent studies in health sciences are based on more than 20,000 observations, as they rely on large longitudinal datasets such as the Survey of Health, Ageing and Retirement in Europe (SHARE) database ( Litwin et al, 2018 ; Litwin & Levinson, 2018 ) and the Canadian Longitudinal Study on Aging ( Demnitz et al, 2018 ), containing micro-data on health status of older adults.…”
Section: Resultsmentioning
confidence: 99%
“… OUTCOME VARIABLES DISCIPLINE MOBILITY MEASURE(s) AUTHOR(s) Clinical Medicine LSA test ( Baker et al, 2003 ) (−) Lo et al (2016) Self-reported information – Perceived difficulty and task modification in advanced mobility regarding the 2-km walk (−) Manty et al (2012) Self- reported information - Questions on difficulties with walking or climbing stairs (−) Musich et al (2018) Self-reported information – Reported grade of difficulty (no difficulty vs some difficulty, moderate difficulty, severe difficulty) getting about outdoors (−) Jefferis et al (2015) Falls TUG test and Mobility Scores (Gait Composite Score, Balance Composite Score, Physical Capacity Score) (n) Langeard et al (2019) N = 19.3% TUG test (−) Dai et al (2012) (11/57) Public Health & Health Services TUG test, DGI, SPPB and CB&M (−) Balasubramanian et al (2015) TUG test (n) Mulasso et al (2016) Composite scores of individual mobility variables such as quiet standing, maximal lean, sit-to-stand, gait, turn, step-in-tub and downstairs (−) Panzer et al (2011) TUG test, Timed Chair Stand test, Functional Reach test, One-Leg Balance test, and lower limb muscle strength (−) Topuz et al (2014) Self-reported information - List of 10 difficulties such as getting up from a chair after sitting for long periods, climbing one flight of stairs without resting, and stooping, kneeling, or crouching, etc. (−) Litwin et al (2018) Clinical Medicine …”
Section: Resultsmentioning
confidence: 99%
“…As complicaçÔes de maior impacto para a vida do idoso apĂłs FFP na sua grande maioria dos casos sĂŁo ocasionadas por quedas posteriores. Assim, medidas preventivas que evitem suas consequĂȘncias necessitam ser adotadas para que sua ocorrĂȘncia seja reduzida (Litwin et al, 2018). A prĂĄtica de exercĂ­cios fĂ­sicos regulares pĂłs-operatĂłria de FFP Ă© defendida por vĂĄrios autores com objetivo de melhorar a autonomia deste paciente, melhorando sua postura e o equilĂ­brio corporal, melhora da marcha, alĂ©m da promoção do fortalecimento e aumentar a massa muscular desses indivĂ­duos (CamĂ”es et al, 2016).…”
Section: Resultsunclassified